VIDEO GAMES: AN INNOVATIVE WAY TO MASTER ENGLISH - Dina Rafidiyah; Muhammad Julian Adhitama; Denny Wianto (UMBanjarmasin, 2019)
The best way to learn a language is by immersing yourself into it. One way to immerse into English is by using video games as one of the innovative ways to master English. This media enables gamers to get exposed to the target language since they play it for long times. The aim of this paper is to find out the reason why the subjects of the present research play video games and how it can help them to learn English. Lastly, this paper also wants to find out how viable applying video game in classroom’s lesson. The research methodology is phenomenology approach. The data were garnered from in-depth interview, the participants answered the questions correctly and coherently to be considered having good English. Subjects of this research are six people with different backgrounds; they were united by their love of video games and their use of English in video games online community. The results of this study were the subjects play video game to entertain themselves through gameplay, story-driven, competitiveness of the game, interaction with other players and releasing stress. All participants agreed that video games help much in improving their English ability. Almost all participants considered that video games could be brought ito English classes, with some considerations